Faculty perception on clinical shadowing: A concurrent mixed methods study. Issue 4 (30th November 2022) - Chaitanya, Penmatsa; Bhadila, Ghalia; Dragan, Irina F.
Abstract: Purpose: This mixed methods study aims to investigate faculty members' perceptions of early clinical exposure through clinical shadowing program (CSP) at one academic dental institution. Methods: After ethical approval was received, concurrent data collection using quantitative and qualitative methods was integrated for this study design. For the quantitative data, a validated instrument (Likert scale) was distributed to all basic and clinical science faculty members regarding the CSP. Qualitative semi‐structured interviews of basic and clinical science faculty members were conducted to explore their perceptions of the CSP. Descriptive statistics were completed for the quantitative data, and thematic analysis was carried out for the transcribed interviews. Results: Faculty members from basic and clinical sciences participated in this mixed methods study, 97% ( n  = 74) participants in the quantitative and 12 participants in the qualitative. The majority of faculty (67%; n  = 44) strongly agreed that CSP helps predoctoral students in the application of basic science knowledge to clinical practice. All basic science respondents ( n  = 10; 100%) and many clinical science faculty (60%; n  = 35) strongly agreed that CSP requires coordination between basic and clinical science educators ( p  = 0.042). Some faculty suggested the inclusion of training for educators on the program and regular periodic student assessments of the program's effectiveness. Conclusion: The current study reported positive faculty perception toward the proposed method of integration. Furthermore, opportunities to foster coordination between basic and clinical science educators may be provided by administrators to strengthen the existing CSP framework.